Introducing decisive development orientations into transport modelling - Tanczos, Katalin; Torok, Arpad (Transport, 2008)
To effectuate a consistent methodology for urban planning taking into consideration the viewpoints of land use and transportation, we need to approach the subject and consider complex social and economical aspects. To handle both of the above mentioned urban planning areas, we shall develop models able to pay attention to all of their restrictive factors within temporal properties.First published online: 27 Oct 2010